Characterization of antioxidant, antimicrobial, anticancer property and chemical composition of ficus deltoidea jack. leaf extract - Lee Seong Wei; Wendy Wee (2011)
This paper described antimicrobial, antioxidant and anticancer activities of Ficus deltoidea Jack. Leaf extract as well as its chemical composition. The main objective of the present study was to reveal the potential of f.deltoidea leaf to be used as medicinal drug.